(untitled) (Interdisciplinary Studies Journal, 2024)
Female leadership has become a central theme in national and international discussions, especially within the context of Brazilian Public Administration, where gender representation has gained greater relevance in recent decades. This study aims to present an overview of female leadership in the Brazilian public sector, using a Systematic Literature Review (SLR) as the methodology, covering the period from 2018 to 2023. The research followed the protocol by Cronin, Ryan, and Coughlan (2008) and was conducted across scientific databases such as Scielo, Web of Science, ScienceDirect, Mendeley, CAPES, Google Scholar, and Scopus. A total of 30 articles were analyzed, addressing key barriers faced by women in leadership positions in the public sector, along with topics such as leadership styles, gender stereotypes, and representativeness. The results indicate that women still face significant challenges in ascending to and performing leadership roles. Based on these analyses, the study proposes directions for future research agendas and supports the formulation of inclusive public policies aimed at promoting gender equality in Public Administration.